2004
DOI: 10.1210/en.2003-0605
|View full text |Cite
|
Sign up to set email alerts
|

Agouti-Related Protein Antagonizes Glucocorticoid Production Induced through Melanocortin 4 Receptor Activation in Bovine Adrenal Cells: A Possible Autocrine Control

Abstract: Agouti-related protein (Agrp), primarily expressed in the hypothalamus, is an endogenous antagonist of alphaMSH at the level of melanocortin 3 receptor (MC3-R) and MC4-R, but the adrenal gland represents the second major Agrp-expressing tissue. In adrenal fasciculata cells, the glucocorticoid secretion is under the control of ACTH, which binds specifically MC2-R, the only functional melanocortin receptor described in these cells to date. Nevertheless, using cultured bovine fasciculata adrenal cells, we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 39 publications
2
16
1
Order By: Relevance
“…We also observed a fasting-induced up-regulation of MRAP mRNA in WT mice that did not exist in MC3-R −/− mice. Finally, we monitored AgRP mRNA, because adrenal AgRP expression is up-regulated during a fast and is thought to play a role in controlling corticosterone release (43,44). Similar to both MC2-R and MRAP, AgRP mRNA was up-regulated by fasting in WT mice but not in MC3-R −/− mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed a fasting-induced up-regulation of MRAP mRNA in WT mice that did not exist in MC3-R −/− mice. Finally, we monitored AgRP mRNA, because adrenal AgRP expression is up-regulated during a fast and is thought to play a role in controlling corticosterone release (43,44). Similar to both MC2-R and MRAP, AgRP mRNA was up-regulated by fasting in WT mice but not in MC3-R −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a non-CRH-mediated mechanism leading to elevated basal corticosterone in the MC3-R −/− is possible also. In fact, it is possible that MC3-R deletion from the adrenal gland results in hypercorticosteronemia by eliminating the ability of AgRP to induce its paracrine inhibitory effects on corticosterone (20,44).…”
Section: Discussionmentioning
confidence: 99%
“…From the lack of MC2R expression and the stable MC1R expression they concluded that melanocortins regulate cell proliferation and inflammatory processes rather than lipolysis in human adipose tissue. Although several groups detected different members of the MCR family in a variety of bovine tissues, no data exist for adipose tissue so far [29], [58][60]. In this context we targeted all MCR in bovine SCF.…”
Section: Discussionmentioning
confidence: 99%
“…Both MC3R and MC4R are expressed in rat adrenal gland and can bind ACTH with the same affinity as ␣-MSH (58,177). MC4R is also expressed in human adrenal tissue, whereas MC3R expression has been detected in the human adrenocortical cell line H295R (60). AGRP is present in bovine adrenocortical cells and inhibits both acute and long-term Nle4,D-Phe7 (NDP)-␣-MSH-and ACTH-induced cortisol production by antagonistic action toward MC4R, in addition to inhibiting ACTH-induced longterm cortisol production, in a biphasic manner independent of MC2R (59 -61).…”
Section: Glucocorticoids Play An Important Role In Insulin Resistancementioning
confidence: 99%